Trains Detection Using Video Processing Method for Automation Railroad Crossing - Sani, Suhaidee; Chimphet, Teerapong; Sangprasert, Naratorn; Charoennatkul, Charoon (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2020)
This paper presents trains detection by using video processing method for automation railroad crossing. It aims to study method of video processing, adaption in rail transport and developing engineering tools preventing accidents at crossing. The system is designed to detect diesel trains, which have the speed the limited speed posted at 120 km/h. The system use closed circuit TV cameras (CCTV), which were installed on the side of the railroad in 1 km from the crossing, to supports data recording. Data of video processing of trains will pass on fiber optic cable to a computer system. Then, processing of image of trains by program, which were developed by trains detection function which consists of color threshold function, pattern matching function and motion gauge function. When the system can identifiy objects that are trains, the system will sent signal control to railroad crossing. The results showed that the trains detection system works well with diesel trains and is a exact tool when the trains moving into distance 50 m from closed circuit TV camera (CCTV) and the railroad crossing works before the trains moving arrive at the crossing. The finding shows method of video processing could be an accident prevention on the rail road tool, decreasing dependence hight priced technology and it is a research in supporting the sustainable development railroad transportation system in Thailand.